The laparoscopic repair of inguinal hernia in female children in the Republic of North Macedonia - Toni Risteski (Serbian Medical Society, 2021)
Introduction/Objective. Laparoscopic inguinal hernia repair in children is a minimally invasive method, and with its safety, feasibility, and excellent cosmesis is an acceptable alternative to open repair. Methods. This is a prospective clinical study, with national data of 49 female children aged 1–14 years, treated via laparoscopic approach. Operative time, time to verticalization (normal position in bed, standing/ walking), hospital stay, nausea, pain, and cosmetic effects (size and visibility of the mark) were elaborated. Results. The results revealed that five (10.2%) children had a family history of inguinal hernia. A total of 29 (59.2%) children had hernia located on the right side, 19 (38.8%) on the left side, and one (2%) on both sides. The average diameter of the inguinal opening was 3 ± 2.17 cm. Sixteen children (32.7%) had hidden hernia. The average operation time of the unilateral intervention was 29.5 ± 6.8 minutes, and for bilateral hernias it was 43.6 ± 7.2 minutes. The average length of hospitalization was 14.1 ± 3.1 hours, and the time needed for a full return to a normal position in bed was 2.6 ± 0.6 hours. The average length of the scar in both the right and the left groin region was 2.2 ± 0.4 mm. A total of 46 (93.9%) parents/guardians were satisfied by the esthetic result, while three (6.1%) had no particular opinion regarding this question. Conclusion. The introduction of laparoscopic surgery in the treatment of inguinal hernia is a promising method, which plays an important role as an alternative surgical technique because of the minimal invasiveness of the technique and improved recovery of the children.
Keywords: children’s inguinal hernia; PIRS - percutaneous internal ring suturing; minimal invasive surgery